Generation of a Mouse Model to Study the Noonan Syndrome Gene Lztr1 in the Telencephalon - Talley, Mary Jo; Nardini, Diana; Shabbir, Nisha; Ehrman, Lisa A.; Prada, Carlos E.; Waclaw, Ronald R. (Frontiers in Cell and Developmental Biology, 2021)
The leucine zipper-like transcriptional regulator 1 (Lztr1) is a BTB-Kelch domain protein involved in RAS/MAPK pathway regulation. Mutations in LZTR1 are associated with cancers and Noonan Syndrome, the most common RASopathy. The expression and function of Lztr1 in the developing brain remains poorly understood. Here, we show that Lztr1 is expressed in distinct regions of the telencephalon, the most anterior region of the forebrain. Lztr1 expression was robust in the cortex, amygdala, hippocampus, and oligodendrocytes in the white matter. To gain insight into the impact of Lztr1 deficiency, we generated a conditional knockout restricted to the telencephalon using Foxg1IREScre/+. Lztr1 cKOs are viable to postnatal stages and show reduced Lztr1 expression in the telencephalon. Interestingly, Lztr1 cKOs exhibit an increase in MAPK pathway activation in white matter regions and subsequently show altered expression of stage specific markers in the oligodendrocyte lineage with increased oligodendrocyte progenitor cells and decreased markers of oligodendrocyte differentiation. Moreover, Lztr1 cKOs also exhibit increased expression of the astrocyte marker GFAP. These results highlight the generation of a new mouse model to study Lztr1 deficiency in the brain and reveal a novel role for Lztr1 in normal oligodendrocyte and astrocyte development in the telencephalon.